Analysis of Physical Growth and Motor Development in Early Childhood (Universitas Pendidikan Indonesia, 2024)
Physical growth and motor development in early childhood are critical for shaping long-term health and cognitive abilities. Research has extensively examined Body Mass Index (BMI), arm span, leg length, and motor skills as key indicators of a child physical growth and competence. However, discrepancies between physical growth and BMI, particularly in underweight children, remain poorly understood. This study aimed to assess the physical growth and motor development of kindergarten children, focusing on BMI, arm span, leg length, gross motor skills, and fine motor skills. A quantitative descriptive approach was employed, utilizing measurements of BMI, arm span, and leg length. The assessments of gross and fine motor skills using standardized tests were also administered. Data were analyzed to determine the minimum, maximum, and mean values for each variable. Frequency distributions were used to categorize BMI and motor skill levels. The results showed that 75% of the children were underweight, despite average arm span and leg length measurements falling within normal ranges. In motor skills, 83.3% of the children exhibited very good fine motor skills. Meanwhile, the gross motor skills of the students were primarily in the average to above-average category. In conclusion, the study revealed a significant prevalence of underweight children, despite normal physical growth indicators, suggesting potential nutritional concerns. The findings highlight the need for further investigation into the socio-economic and dietary factors affecting a child development and for targeted interventions to support the enhancement of both physical growth and motor skills.